2018
DOI: 10.4328/jcam.5740
|View full text |Cite
|
Sign up to set email alerts
|

Gastric adenomyoma determined incidentally during sleeve gastrectomy: A case report

Abstract: Gastric adenomyoma is a rare benign tumor, characterized by gland-like structures embedded within a smooth muscle stroma. We report the case of a 26-year-old woman with a body mass index (BMI) of 51 kg/m2 who was not having any metabolic diseases was prepared for obesity surgery. No pathologies were detected in the abdominal ultrasound or upper gastrointestinal system endoscopy taken before the operation. Abdominal computerized tomography was obtained which revealed a nodular lesion causing mural thickening on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…In 2017, Emerson et al [ 7 ] have reported that 17 of the 571 cases that could not be fully resected by endoscopic submucosal dissection were GA, while these data contained no pathological images. Even if these lesions are indeed GA, as well as those who did not undergo operations and thus had no definitive diagnosis, a consensus has been reached that GA is an uncommon disease[ 8 - 10 ]. GA has occurred in all age groups, from 7 d[ 8 ] to 84 years[ 9 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In 2017, Emerson et al [ 7 ] have reported that 17 of the 571 cases that could not be fully resected by endoscopic submucosal dissection were GA, while these data contained no pathological images. Even if these lesions are indeed GA, as well as those who did not undergo operations and thus had no definitive diagnosis, a consensus has been reached that GA is an uncommon disease[ 8 - 10 ]. GA has occurred in all age groups, from 7 d[ 8 ] to 84 years[ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…GA has occurred in all age groups, from 7 d[ 8 ] to 84 years[ 9 ]. To some extent, its low occurrence rate is because the majority of these cases are asymptomatic[ 10 - 12 ]; however, some GA patients experience epigastric pain and discomfort, with/without nausea[ 13 ], vomiting[ 14 ], dyspepsia[ 15 ], and melena[ 16 ]. Concerning small children or infants, the first symptom may be nonbilious vomiting[ 8 , 13 - 14 , 17 - 19 ] or esophageal reflux[ 20 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They most often occur in adults, although there are rare case reports of these lesions in children [2]. The majority of gastric adenomyomas are an incidental/asymptomatic finding in patients being evaluated for nonspecific gastrointestinal symptoms [3,4]. Rarely, they present with melena and in children, some cases reportedly mimicked gastric duplication cysts, pyloric stenosis, or caused gastric outlet obstruction [1,[5][6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%